PENGARUH KARAKTERISTIK INDIVIDU DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA - Bustomi, Syahrul; Purbangkoro, Murdjianto; Nurhardjo, Budi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2015)
Abstract: This research is a survey research with the objective of analyzing whether individual characteristic, organizational commitment, and job satisfaction influence employee performance inPT Bank Rakyat Indonesia (Persero) Tbk, Surabaya. The model used in this study was causality model. The hypothesis were tested using path analysis. The sample consisted of 102 respondents. Results showed that individual characteristics, organizational commitment, and job satisfaction had significant influence on employee performance. Keywords: Individual Characteristic, Organizational Commitment, Job Satisfaction, Employee Performance.